Blood anti-surface proteins Echovirus 30 (Enterovirus, Picornaviridae) antibodies in residents of the Nizhny Novgorod region - Dmitrii A. Melentev; D. V. Novikov; V. A. Lapin; E. V. Mokhonova; М. I. Tsiganova; E. A. Manakova; V. V. Novikov (Инфекция и иммунитет)
Echovirus 30 (Е30) is an enterovirus that causes severe forms of serous meningitis. Over many years, E30 virus has caused serous meningitis outbreaks all over the world including Russia, but the status of anti-E30 population immunity remains unexplored. In 2022, the average percentage of all pediatric admission enterovirus cases in Russia was 97%; the most severe E30 infection cases were registered in children under 17 years of age. The virus capsid surface contains proteins VP1, VP2 and VP3 with homologous epitopes common to other enterovirus proteins, which allows them to be used as an antigen for antibody detection. The work was aimed at assessing frequency of different antibody classes specific to full-length recombinant E30 VP1, VP2 and VP3 proteins. 331 blood serum samples collected from 2 months-to 61 year-old residents of the Nizhny Novgorod region were used in the study. E30 VP1, VP2 and VP3 proteins were expressed in Escherichia coli, purified chromatographically and used antigenically for detection of IgA, IgG and IgM antibodies by using enzyme-linked immunosorbent immunoassay. Most study subjects had antibodies specific to only one or two of the E30 surface proteins. IgA, IgG and IgM antibodies to three recombinant proteins were detected simultaneously in 0.3%, 4.2% and 2.7% of cases. Totally, anti-E30 protein IgG antibodies were detected in 29.9% of cases. The maximum detection rate of antibodies (50.0%) was recorded in pediatric groups that decreased with age. IgG antibodies were found in 9.3% of the tested individuals. The detection rate (16.6%) peaked in the age group of children from 7 to 11 years. The IgM antibody-obtained data evidence that during the study period, almost one in every ten-study participant was infected with enteroviruses. The results of analyzing long-term immunity specific to enteroviral proteins showed the highest frequency of detected IgG antibodies in children that tended to decline with age as well as about continued E30 virus circulation in the Nizhny Novgorod region.